Validity of a self‐reported questionnaire for periodontitis in a Spanish population - Saka‐Herrán, Constanza; Jané‐Salas, Enric; González‐Navarro, Beatriz; Estrugo‐Devesa, Albert; López‐López, José (Journal of periodontology (1970), 2020)
Background Clinical examination is the gold‐standard approach for surveillance of periodontitis; however, it requires large resources. Several self‐reported measures have been developed and tested in diverse scenarios with results suggesting that it may be a useful tool for screening periodontal disease in different populations; yet they have not being tested in Spanish population. We aimed to assess the validity of a self‐reported questionnaire for periodontitis in a Spanish population from Barcelona during 2018. Methods One hundred and twelve participants were enrolled in the study and, in one appointment; a dentist performed the self‐reported questionnaire and a full‐mouth periodontal examination. Periodontitis was defined as at least mild periodontitis according to three criterion of classification. Receiver‐operating characteristics curve analyses were used to test the discriminatory capability, sensitivity and specificity of the self‐reported questionnaire and logistic regression models were adjusted to estimate the minimal‐set of questions associated with periodontitis. Results The self‐reported questionnaire had a useful discriminative capability for detecting individuals with periodontitis (area under the curve [AUC] = 0.85 95% CI 0.78‐0.92) and its moderate/severe form (AUC = 0.86 95% CI 0.79‐0.04) with sensitivity and specificity of 77% and 74% and 73% and 87%, respectively; representing moderate validity. The combination of four‐specific questions had high accuracy (AUC = 0.88 95% CI 0.81‐0.94) and validity (sensitivity = 92.2%) and was strongly associated with moderate/severe periodontitis after adjusting by socio‐demographic factors. Conclusions The use of several self‐reported questions proved to have a good performance for screening periodontitis in the population under study; specifically, those related with tooth mobility and gum migration. Large community‐based studies are needed to test its validity and predictive capability.